Information System for Batik Small and Medium Enterprises (SMEs): Implementation of 3D Maps as a Means of Promotion and Ease of Access to Information - Wahyuningrum, Dwi; Alfiani, Oktavia Dewi; Arfianto, Nasrul (Institut Teknologi Bisnis AAS Indonesia, 2025)
Competition to improve and optimize existing systems to achieve targeted results in an industrial ecosystem is increasingly fierce. This also applies to the Micro, Small, and Medium Enterprises (MSMEs) in Yogyakarta's batik industry. From the consumer's perspective, access to location information is crucial for evaluating the conditions and products of MSMEs. On the other hand, for MSMEs, an increase in consumer visits translates to higher sales. Facilitating the availability of information is a key strategy to attract more visitors to MSMEs, both through direct visits to physical stores and virtually via online shopping platforms. One critical type of information is spatial data (space/position), which consumers use to locate MSMEs. A technological approach, such as website-based spatial access, is expected to meet this need. This study aims to enhance the accessibility of information for all stakeholders, including consumers and other participants in the batik industry ecosystem. It also enables batik MSMEs to optimize promotional strategies, increasing visitor numbers and product sales. This research applied the concept of 3-dimensional visualization to represent the locations of Batik MSMEs in Yogyakarta City and developed an information system for these businesses. The data includes spatial data and attributes, such as a list of MSMEs and detailed information. The information system was developed by integrating MSME location data with MapboxGL (a web app service) to provide a realistic 3D visualization of MSME locations. The final output is a website-based information system freely accessible online to various stakeholders, including consumers, policymakers, and institutions.